2022
DOI: 10.3390/photonics9120887
|View full text |Cite
|
Sign up to set email alerts
|

Non-Radiative Transitions of Holes on Mercury Vacancies in Narrow-Gap HgCdTe

Abstract: Mercury vacancies, acting as double acceptors, are the dominant point defects in ternary HgCdTe alloys. Though HgCdTe is one of the leading materials in infrared optoelectronics, the energy spectra of the vacancies are still a matter of some debate. This work investigated the rates at which holes are captured to a singly ionized mercury vacancy via acoustic phonon emission in narrow-gap Hg1−xСdxTe with technologically relevant x~0.22. Combined with the calculated rates of intracenter transitions, the data allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 28 publications
0
7
0
4
Order By: Relevance
“…-время заполнения. Здесь τ (E) -время перехода дырок между состояниями с энергией E и E 0 при испускании акустических фононов, рассчитанное методом из работы [14]. Видно, что для трех описанных состояний времена спонтанного безызлучательного заселения меньше времен опустошения, что должно приводить к накоплению дырок на этих уровнях и появлению сигнала ФЛ при излучательных переходах дырок на основное состояние.…”
Section: результаты и обсуждениеunclassified
See 3 more Smart Citations
“…-время заполнения. Здесь τ (E) -время перехода дырок между состояниями с энергией E и E 0 при испускании акустических фононов, рассчитанное методом из работы [14]. Видно, что для трех описанных состояний времена спонтанного безызлучательного заселения меньше времен опустошения, что должно приводить к накоплению дырок на этих уровнях и появлению сигнала ФЛ при излучательных переходах дырок на основное состояние.…”
Section: результаты и обсуждениеunclassified
“…Четвертый столбец τ 2 -время безызлучательного заполнения состояний дырками. Времена рассчитаны с использованием темпов захвата дырок при излучении акустических фононов, полученных методом из работы [14]. Параметры ПЦЯ для расчета состояний двойного акцептора взяты из работы [19].…”
Section: результаты и обсуждениеunclassified
See 2 more Smart Citations
“…In this case, all mercury vacancies in the absence of illumination were in the A −2 2 charge state, and A −1 2 -centers, due to which the longest wavelength PL is observed, appeared because of the capture of holes excited by illumination from the valence band to mercury vacancies. In the paper [14] it was shown that the PL spectrum is formed by hole transitions between localized states. Note that in the paper [14] it was sufficient to take into account only spontaneous processes associated with acoustic phonons, the intensity of which weakly depends on temperature.…”
Section: Introductionmentioning
confidence: 99%